Left atrial thrombus and dense spontaneous echocardiographic contrast in patients on continuous direct oral anticoagulant therapy undergoing catheter ablation of atrial fibrillation: Comparison of dabigatran, rivaroxaban, and apixaban - Wu, Michael; Gabriels, James; Khan, Mohammad; Shaban, Nada; D'Amato, Salvatore; Liu, Christopher F.; Markowitz, Steven M.; Ip, James E.; Thomas, George; Singh, Parmanand; Lerman, Bruce; Patel, Apoor; et al. (Heart rhythm, 2018)
Left atrial thrombus (LAT) and dense spontaneous echocardiographic contrast (SEC) detected by transesophageal echocardiography (TEE) in patients on continuous direct oral anticoagulants (DOAC) therapy before catheter ablation of atrial fibrillation (AF) or atrial flutter (AFL) have been described. We sought to compare rates of TEE-detected LAT and dense SEC among patients taking different DOACs. We evaluated 609 consecutive patients from 3 tertiary hospitals (median age 65 years; interquartile range 58–71 years; 436 (72%) men) who were on ≥4 weeks of continuous DOAC therapy (dabigatran, n = 166 [27%]; rivaroxaban, n = 257 [42%]; or apixaban, n = 186 [31%]) undergoing TEE before catheter ablation of AF/AFL. Demographic, clinical, and TEE data were collected for each patient. Despite ≥4 weeks of continuous DOAC therapy, 17 patients (2.8%) had LAT and 15 patients (2.5%) had dense SEC detected by TEE. The rates of LAT were 3.0%, 3.5%, and 1.6% for patients on dabigatran, rivaroxaban, and apixaban, respectively (P = .482). The rates of dense SEC were 1.2%, 3.5%, and 2.2% for patients on dabigatran, rivaroxaban, and apixaban, respectively (P = .299). Congestive heart failure (odds ratio 4.4; 95% confidence interval 1.6–12; P = .003) and moderate/severe left atrial enlargement (odds ratio 3.1; 95% confidence interval 1.1–8.6; P = .026) were independent predictors of LAT. In this study, ∼3% of patients on continuous DOAC therapy had LAT detected before catheter ablation of AF/AFL. Specific DOAC therapy did not significantly affect the rates of LAT detection.